Prognostic differential subpopulation classification and immunotherapy response prediction in pancreatic cancer patients based on the gene features of necrotizing apoptosis - Liao, Kaili; Fu, Zheng; Liu, Xinrui; Yu, Xiajing; Jin, Linfeng; Cheng, Jinting; Yang, Dongyu; Ai, Kun; Liu, Ziqian; Guo, Daixin; Liu, Shuai; Yan, Xiwen; et al. (Frontiers in Immunology, 2025)
IntroductionThis study aims to explore the prognostic significance of necroptosis-related genes in pancreatic cancer.MethodsFirst, clustering analysis was performed on 15 necroptosis-related genes, which led to the identification of two distinct NRG subtypes. Differential expression analysis revealed 495 genes associated with prognosis, which were subsequently used for a second round of clustering. Next, a prognostic model was constructed using seven key genes, and patients were classified into high-risk and low-risk groups. External cohort data were used to validate the prognostic model. Spearman correlation analysis was conducted to examine the relationship between the most important biomarker, CHST11, and the 15 NRG genes. Additionally, three single-cell datasets, along with Mendelian randomization and spatial transcriptomics analyses, were utilized to further investigate the associations between CHST11, immune therapy, immune cells, and malignant epithelial cells.ResultsNRGcluster A and geneCluster B largely overlapped, with most patients classified into the low-risk group. Among the 15 NRG genes, 11 exhibited significant expression differences between the high-risk and low-risk groups. CHST11 was identified as the most important prognostic biomarker and showed significant correlations with 13 NRG genes. Further analysis revealed potential mechanisms of action for CHST11.DiscussionThis study, through multi-omics data, reveals that CHST11 may be associated with necroptosis and is closely related to the malignant prognosis of pancreatic cancer.